The Effect of Ambidextrous Leadership on Employee Performance: The Mediating Role Of Innovative Behavior and Work Engagement - Javeid, Muhammad Saad (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
This study investigates the influence of ambidextrous leadership on employee performance in Pakistan’s retail sector, with a focus on the mediating roles of innovative work behavior and work engagement. Ambidextrous leadership, which involves balancing exploratory (innovation-oriented) and exploitative (efficiency-oriented) behaviors, is increasingly recognized as vital for organizational success in dynamic environments. Drawing on organizational behavior and leadership theories, this research adopts a quantitative approach, utilizing a structured questionnaire to gather primary data from 161 employees across various hierarchical levels in retail organizations. The survey incorporates validated scales for ambidextrous leadership, innovative work behavior, work engagement, and employee performance. Data were analyzed using Structural Equation Modeling (SEM) to examine the direct and indirect relationships among the variables. The findings reveal that ambidextrous leadership significantly enhances employee performance both directly and indirectly through increased engagement and innovation. This highlights the critical role of leadership in fostering a proactive and committed workforce. The study contributes to leadership and organizational behavior literature by providing empirical evidence from an emerging market context. Furthermore, it offers practical insights for managers aiming to improve performance by adopting a flexible leadership style that encourages both innovation and task efficiency. Limitations and future research directions are also discussed.